Correlation Between the Severity of Neurological Deficits in Patients with Symptomatic Spinal Metastases and Short-Term Postoperative Functional Neurological Improvements - Hessler, C.; Madert, J.; Heese, O. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Objective The correlation between the severity of neurological deficit of patients with symptomatic spinal metastases and short-term, postoperative, functional improvements after surgery is unclear. The aim of this clinical trial was to determine the influence of neurological deficit severity on short-term functional outcomes after surgery, and to devise optimal treatment strategies for this patient population.Methods Between 01/1999 and 12/2004, 194 patients with symptomatic spinal metastases were surgically treated. Each patient underwent neurological examination pre- and postoperatively. The results were ranked according to the Frankel score. The pre- and postoperative Frankel score was compared in order to assess the development of neurostatus following a surgical procedure.Results Complete postoperative remission was seen in 27% of all patients (27/101) with a preoperative Frankel score D, as well as in 5% of all patients (4/77) with a preoperative Frankel score C. Improvement of the preoperative neurologic deficits occurred in 27% of all patients (27/101) with a preoperative Frankel score D, 58% of all patients (45/77) with a preoperative Frankel score C, 36% of all patients (5/14) with a preoperative Frankel score B, and 50% of all patients (1/2) with a preoperative Frankel score A.Conclusion Surgical treatment of patients suffering from neurological deficits caused by spinal metastases results in neurological function improvements. The probability of neurological improvement does not correlate with the severity of the preoperative neurologic deficit. As a consequence, the decision to operate on these patients should not depend on the severity of pre-operative neurological symptoms alone.
Keywords: metastases; surgery; neurological outcome; spine